2022
DOI: 10.1155/2022/8111022
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Links between Stress, Brain Injury, and Disease

Abstract: Stress, which refers to a combination of physiological, neuroendocrine, behavioral, and emotional responses to novel or threatening stimuli, is essentially a defensive adaptation under physiological conditions. However, strong and long-lasting stress can lead to psychological and pathological damage. Growing evidence suggests that patients suffering from mild and moderate brain injuries and diseases often show severe neurological dysfunction and experience severe and persistent stressful events or environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 171 publications
0
8
0
Order By: Relevance
“…Psychological stress has been associated with adverse health outcomes [ 150 ], especially neurological disorders as it can exacerbate neuroinflammatory processes ( Figure 2 ) [ 151 , 152 , 153 ]. The proposed mechanism of this psychosocial determinant of health is, in part, due to priming microglia and inflammatory responses, which contribute to cognitive deterioration [ 154 ].…”
Section: Additional Factors Impacting Neurological Effects Of Covid-19mentioning
confidence: 99%
“…Psychological stress has been associated with adverse health outcomes [ 150 ], especially neurological disorders as it can exacerbate neuroinflammatory processes ( Figure 2 ) [ 151 , 152 , 153 ]. The proposed mechanism of this psychosocial determinant of health is, in part, due to priming microglia and inflammatory responses, which contribute to cognitive deterioration [ 154 ].…”
Section: Additional Factors Impacting Neurological Effects Of Covid-19mentioning
confidence: 99%
“…The detrimental impact of psychological stress on neurons has become an increasingly pressing concern. The oxidative stress response has long been proposed as a plausible mechanism linking stress to various pathological changes [ 7 , 11 , 12 ]. The accumulation of reactive oxygen species (ROS) has been evidenced in various animal stress models, and a great imbalance of the pro-oxidant/antioxidant ratio has been observed in different organs, particularly brain tissues, of stressed animals [ 8 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stress is used to refer to a condition where various or perceived stimuli alter the homeostatic state of an organism [7] , which regular accompanies with patients and exists in the process of disease therapy. Stress has an important role in the occurrence and development of various consider able diseases among cardiovascular [8] , digestive [9] , immune [10] , and nervous system [11] .A number of early reports have suggested that stress serves a major role in the initiation, course and outcome of liver diseases.…”
Section: Introductionmentioning
confidence: 99%